Musculoskeletal symptoms in formal and informal caregivers of elderly people - Leandro Corrêa Figueiredo; Aline Cristina Martins Gratão; Gustavo Carrijo Barbosa; Diana Quirino Monteiro; Lucas Nogueira de Carvalho Pelegrini; Tatiana de Oliveira Sato (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to evaluate musculoskeletal symptoms in formal and informal caregivers of elderly people, and check association with personal and work-related factors. Methods: this is a cross-sectional study. Instruments for assessment were the International Physical Activity Questionnaire, Self-Reporting Questionnaire-20, Borg's effort perception scale and Nordic Musculoskeletal Questionnaire. Results: informal caregivers had been working for a longer time (60.2% vs. 41%), had more hours of work (37.4% >12h for day), less time off (85.4% vs. 2.5%) and lack of care guidelines (90.2%). The region with the most musculoskeletal symptoms was the spine and the greater dependence of the elderly, the greater the chances of developing musculoskeletal symptoms (OR= 1.3, 95% CI= 1.1-1.6, p <0.05). Conclusion: personal and work-related factors were more prevalent in informal group and the elderly person's dependence interferes with the increase in musculoskeletal symptoms of caregivers.